Hours of Opportunity, Volume 1 Lessons from Five Cities on Building Systems to Improve After-School, Summer School, and Other Out-of-School-Time Programs - Bodilly, Susan J. (RAND Corporation, 2010)
The Wallace Foundation sponsored an initiative to help five cities increase collaboration, access, quality, information sharing, and sustainability in their out-of-school-time systems. The first in this three-volume series describes the cities' early work under the grant and analyzes the conditions and activities that contributed to their progress in building a coordinated system of services to meet the initiative's goals.